The Sense Lies in the Detail. Nehrlich's Study about Typographic Features in Kleist's Prose (KULT_online, 2014)
Nehrlich’s survey Zu Funktion und Bedeutung typographischer Textmerkmale in Kleists Prosa provides an important contribution to the research of Kleist as well as interesting new aspects of the current studies of notational iconicity focusing on materiality and visibility of writing. Typographical features like black letter, letter-spacing, ligature, and punctuation in the authorized release of Kleist’s Erzählungen (1810/11) are the initial points of Nehrlich’s analysis. He states convincing new results and proffers a differentiated impression of scripture-understanding during Kleist’s time. His connections of interpretation and edition draw attention to the face of historical printed texts and typographically guided reading processes.